Hysteresis and the natural rate of unemployment in Ireland - Lee, George (Statistical and Social Inquiry Society of Ireland, 1990)
Conventional Keynesian or Classical macroeconomic theories must be considered inadequate to explain unemployment experiences such as the Irish one. Rigidities that one might associate with fixed contracts, or even adjustment costs in relation to prices or quantities, can hardly account for 17 years of rising unemployment. Indeed, surely such an upturn in conjunction with the apparent breakdown of the unemployment-inflation relationship serves to challenge the existence in Ireland of a stable "natural" rate of unemployment towards which the economy would gravitate and at which the level of inflation would remain constant. Within this context it is compelling to consider the existence of hysteresis in the labour market - i.e. the possibility that an increase in umemployment could have a direct impact on the natural rate or, to put it another way, that this year's equilibrium unemployment depends upon last year's actual rate. This paper examines the presence of hysteresis in the Irish labour market and in so doing enables estimates for the Irish natural rate of unemployment to be calculated. In all cases the long-term equilibrium rate of unemployment is considered to be the same as the natural rate. In Section 2 competing explanations for the hysteresis phenomenon, specifically physical capital, human capital and insider (union members)-outsider (non-union members) explanations are discussed. The following section briefly considers some econometric issues which may arise in the presence of hysteresis while Section 4 is concerned with some discrete time dynamics associated with the natural rate of unemployment. In Section 5 a procedure for testing for hysteresis is derived from the analysis in the preceding two sections. The paper then goes on to apply this test to Irish data and discusses the implications of the results. Since no such work has been done in an international context, it was not possible to compare the Irish outcome with that for other economies. In so far as possible mathematical considerations are dealt with in the appendices.
Barrington Lecture 1989/1990
Read before the Society, 23rd November 1989
Keywords: Unemployment rate; National economy; 314.15